FUENTES DE INFORMACIÓN Y PLURALISMO POLÍTICO EN LA COBERTURA DE ASUNTOS EUROPEOS EN TELEVISIÓN - Dra. Samia BENAISSA PEDRIZA (Fonseca, Journal of Communication, 2023)
The research analyses the use of information sources in television news on European issues and its relationship withpolitical pluralism and pluralism of information through direct observation of a sample of selected stories. The results reveal that political and governmental representatives still occupy a relevant position in the informative space.In addition, the visibility of those sources is enhanced my means of individual appearances given on camera and through text-picture correspondence.